(untitled) (KASBIT Business Journal, 2021)
A supply chain consists of the organization, people, resources, and information involved in moving a product or service from supplier to customer. Transportation is the major function of a supply chain, which provides the movement of products. The purpose of this paper is to analyze the impact of transportation systems on the logistic chain of the dairy company. The collection of milk is a major problem still faced by the dairy sector. Bridging the gap between costs and routing problems simultaneously by forming an effective and efficient route of milk collection network for the dairy processor is a problem faced by the dairy sector in Pakistan because a major part of the cost is associated with it. Previous work has not considered such a real scenario with 62 milk collection centers. This research was considered to describe the importance of transportation systems in the logistics chain to logistics managers, planners, transportation managers so that comprehensive procedures can be made and implemented for reduction of transportation cost of the company to improve the logistics chain. For this, the technique of operations research including minimum spanning tree was used to obtain optimized results.